Nigeria’s Peacekeeping Missions: A Study of Nigeria’s Foreign Policy - Okorafor, Victoria Chimamaka (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
ABSTRACT: The preponderance of peacekeeping in international relations discourse cannot be overlooked. Nigeria has enunciated her appreciation and her attitude towards this United Nations machinery. This research resolves to investigate Nigeria’s peacekeeping exploits. Concurrently, the inspirations for her involvement will be portrayed, especially noting the rate of her contributions since her independence. The examination of Nigeria’s foreign policy, which has been described as Afrocentric in nature, and peacekeeping will be observed, in an attempt to depict a connexion between the two. The impediments faced by this Western African state in achieving peace internationally, most notably the Boko Haram insurgency within her borders, will be viewed including the impact of her pacifist participations. With the aid of primary sources, secondary data and democratic peace theory, this study utilises comparative analysis by contrasting between several missions, specifically in Africa and headed by different international organisations to show the extent of the country’s endeavours. The motivations for intervention have remained almost the same; yet, the rate of peacekeeping involvements was discovered to have decreased in recent years due to demands for internal security boost in light of Boko Haram attacks. Overall, this research definitively provided insight into Nigeria’s peacekeeping predilections, illustrating why it acquired popularity as a peace leader, despite the challenges faced. Keywords: Peacekeeping, Foreign Policy, Afrocentrism, Democratic Peace, United Nations, Responsibility to Protect (R2P)
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2021. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Political Science and International Relations Department; United Nations - Peacekeeping - Nigeria - Africa; Foreign Relations - Nigeria; Nigeria - Politics and Government - Foreign Policy; Peacekeeping, Foreign Policy, Afrocentrism, Democratic Peace, United Nations, Responsibility to Protect (R2P)